Methods to test and generate the wear load spectrum of journal bearing in concrete pump. (April 2021) - Zhu, Linbo; Zhu, Yongsheng; Yan, Yuping
Load spectrum is the basis of wear analysis and life prediction in journal bearing. This paper proposed a method to generate the wear load spectrum from the measured loads that avoiding the errors introduced by the assumptions of traditional constant load. An axle pin load sensor that can recognize the load value and its orientation is developed to test the original wear loads of journal bearing in a concrete pump under working conditions. The interactive influence of perpendicular components in the measured loads is involved by introducing two effect coefficients. Subsequently, the amplitude distribution of the wear load and its lasting time are extracted from the measured complex load-time history using the rain-flow counting method and Weibull distribution. The wear load spectrum is generated by dividing the continuous load into eight load steps. The validity of the approach is supported by finite element analysis on the wear simulation of journal bearing using the generated load spectrum and the measured load. In addition, the effects of load types and load sequence on the wear are discussed based on the proposed method and the FE model. This study provides guidelines to efficiently generate the wear load spectrum for journal bearing, and enhances its reliability of wear prediction in the experimental tests and theoretical analysis.